Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Wolfram Alfa shows $\frac{d}{dx}e^{4y} = 4e^{4y}$

but I do not understand how to get to that answer

I have
$e^{4y} = (e^4)^y$

So by the chain rule is it not the case that \begin{align} \frac{d}{dx}e^{4y} & = y(e^4)^{y - 1}\cdot4e^3 \\ & = y \cdot e^{4y - 4} \cdot 4e^3 \\ & = 4ye^{4y-1} \\ & = \frac{4ye^{4y}}{e} \end{align}

Clearly somewhere I am making a big mess

share|cite|improve this question
up vote 3 down vote accepted

The first thing to note is that you have the derivative with respect to $x$, but $x$ is not in your equation. Technically:

$\frac{d}{dx}e^{4y} = 0$

You should write:


Then we can get that with the chain rule. Let's go through the steps explicitly. $ F = e^{4y}$


$ F = u^{y} $

by saying that $u = e^{4}$.

The chain rule would then be written as:

$ \frac{dF}{dy} = \frac{dF}{du}\frac{du}{dy} $

You have the right result for $\frac{dF}{du}$, but you have an error in $\frac{du}{dy}$. The function $u$ does not contain the variable $y$, so its derivative is zero. That gives you the answer of 0 overall. Clearly that's not right.

What you need to do, when applying the chain rule, is pick a $u$ that is a function of $y$. If you pick:

$u = 4y$, then you get:

$F = e^{u}$

Using the exact same chain rule formula, you can get $\frac{dF}{du}$ and then $\frac{du}{dy}$

share|cite|improve this answer
If you have $u=e^4$, there is no right result for $\frac{dF}{du}$ because there is no $\frac{dF}{du}$ - you can't differentiate w.r.t. a constant! – JiK Apr 2 '14 at 22:39
@JiK, yes, and I should have explained it that way. – James Apr 2 '14 at 22:51

$\frac d{dx}e^x=e^x$

$\frac d{dx}e^y=y'e^y$ - which is an application of the chain rule

$\frac d{dx}a^x=\frac d{dx}e^{x\ln a}=\ln a \cdot e^{x\ln a}=\ln a \cdot a^x$

$\frac d{dx} (e^4)^x=\ln(e^4)\cdot e^{x\ln (e^4)}=4e^{4x}$

share|cite|improve this answer
Maybe you should point out that why his method wont work. That he is infact differentiating with respect to $e$ – Sabyasachi Apr 2 '14 at 19:03
@Sabyasachi You are right - I did think of saying "$e$ is a constant not a variable" – Mark Bennet Apr 2 '14 at 19:07

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.